Jejunal Perforation following Gaelic Football Game - Farhan Shahzad, Muhammad Azam Arif, Adeel Ali Tahir, Mr Amir Siddiqui (Pakistan Journal of Medical & Health Sciences, 2022)
Blunt abdominal trauma leading to jejunal perforation during a football game is very rare, especially in children. This is a case report of this unusual condition is presented under an umbrella of literatures. In-game evaluation did not identify this injury. The athlete completed the game, and the injury was ultimately identified with peritoneal signs and a negative Carnett sign, making abdominal wall injury less likely. The athlete underwent surgical repair of the perforation without complication and has since returned to full activity. It is important to maintain a high index of suspicion and to be observant with serial examinations, advanced abdominal examination maneuvers, and to have a broad differential diagnosis in the case of significant impact to the abdomen during athletics.